FOSTERING CRITICAL THINKING IN ISLAMIC EDUCATION THROUGH PROBLEM-BASED LEARNING IN THE MERDEKA CURRICULUM IMPLEMENTATION - Defi Tri Mulyani; akil akil; Agus Susanto (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to develop students’ critical thinking skills in Islamic education through the implementation of Problem-Based Learning (PBL) within the Merdeka Curriculum. This research used a qualitative approach with data collected through classroom observations, interviews, and documentation of learning activities. The results showed that In conclusion, the integration of the Problem-Based Learning model with religious moral values is empirically proven to significantly boost students' critical thinking and evaluative reasoning through the resolution of real-world social problems. Therefore, the implementation of these five instructional stages ranging from problem orientation to final reflection is highly recommended as a modern, effective framework for transforming character education in the digital age. These findings indicate the need for systematic support for teachers in developing PBL-based learning designs and assessment tools. Schools and policymakers are encouraged to provide professional development programs to strengthen teachers’ pedagogical competencies in implementing the Merdeka Curriculum. Overall, this study confirms that Problem-Based Learning supports the spirit of the Merdeka Curriculum by positioning students as active learners who think critically, reflectively, and contextually in accordance with Islamic values